-(7+2x)=-35+2x

Simple and best practice solution for -(7+2x)=-35+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7+2x)=-35+2x equation:



-(7+2x)=-35+2x
We move all terms to the left:
-(7+2x)-(-35+2x)=0
We add all the numbers together, and all the variables
-(2x+7)-(2x-35)=0
We get rid of parentheses
-2x-2x-7+35=0
We add all the numbers together, and all the variables
-4x+28=0
We move all terms containing x to the left, all other terms to the right
-4x=-28
x=-28/-4
x=+7

See similar equations:

| 7x−40=4.8x+26 | | 5(-9x+8)+x=3+5(3x–7) | | 63=9+6z | | (4x-1(/2=x+7 | | (-7+2x)=-35+2x | | 57-40=x | | 6(1/2x-7=1/3(x-12) | | 3(n+12)=84 | | 28=4x−2 | | 3(4x-2)=2(9x+3) | | 6=4m+5-5m | | 6(-2-7x)=240 | | 35+13=x | | 9x-6+5x-10=180 | | 4x+3=-43 | | 35-13=x | | 16x-15-99=13 | | 60+20s=285 | | -5v+11=8 | | 7x-3(x-8=50(8x+2) | | 57=2(3+r) | | 3(5x−4)^2−25=2 | | 3b+11=5 | | 2x+6x–10=6 | | 2(16+w)=56 | | 10=4/5n-10 | | 2x+6x–10=6 | | 110y+10-11y=1 | | H(t)=-16t^2+40t+15 | | 2a-3=-5 | | 7x-3(x-8=1/2(8x+2) | | .4d+3.1=12.3 |

Equations solver categories